MEKANISME PERTAHANAN DIRI TOKOH PUTRI LANHSIANG DALAM PUTRI BUNGA MEIHUA KARYA CHIUNG YAO - Neni Kurniawati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2008)
Character’s emotions in a romantic novel, the ones represented either through its characters, can be used to analyze the psychological conditions of its characters. The personality condition of a character can be analyzed deeply using the theory of personality system and ego defense mechanism. It also can be applied to Putri Lanhsiang, one of the characters in Putri Bunga Meihua. Her personality system and effort to defend her ego to overcome her anxiety and traumatic experience can be seen clearly using psychoanalytic theory. Several ways such as repression, sublimation, fixation, and self-defense are cathexis used to defend her ego.Keywords: Ego defense mechanism, trauma, personality, fixation,sublimation